Peningkatan Kinerja Membran Polietersulfon (PES) dengan Modifikasi Menggunakan Aditif Hidrofilik - Mustabsyirah Mustabsyirah; Ardhila Shinta; Mirna Rahmah Lubis; Sofyana Sofyana; Mukramah Mukramah; Mukhriza Mukhriza; Wahyu Rinaldi; Umi Fathanah (Jurnal Serambi Engineering, 2022)
Membrane technology has been the methods in the management of clean water, one of polymer that used as membrane materials is polyethersulfone (PES). However, PES is easy to fouling because it is hydrophobic. Fouling will cause a decrease in membrane performance. In this study, PES membrane was modified using hydrophilic additives, namely an alloy of Mg(OH)2 and chitosan. This research study the effect of additives on the performance and anti-fouling properties of the membrane. The membrane preparation was carried out using polymer blending method. The dope solution was made by mixing 18% PES with additives in the form of an alloy of Mg(OH)2 and chitosan with varying compositions of 1% and 5%, with N-methyl-2-pyrrolidone (NMP) as a solvent, and a mixture of ethanol and water as a non-solvent. The membrane characterization was evaluated by analyzing the functional groups. Membrane performance was carried out by measuring the flux and permeability of pure water, selectivity or rejection, as well as membrane anti-fouling tests. From the results of the study, the largest permeability value in PES/NMP membrane with the addition of 5% additive (membrane N5) was 12.9 L/m2.h.bar, rejection was 33.54% with good anti-fouling properties.